LEGAL PROTECTION OF MIS-SELLING CASES VICTIMS ON UNIT LINKED INSURANCE PRODUCTS: THE BASIS OF LAW NO. 40/2014 REGARDING INSURANCE POLICY - Yusuf, Cahaya Firdaus Putri; Wahyuningati, Edi (jfpublisher, 2022)
There are many Indonesian people who want to buy insurance with the most benefits in this modern era. It causes investment-based insurance very popular among community. There are two problem statements of this research, (1) how is the arrangement of mis-selling cases on unit linked insurance products based on Law No. 40/2014 regarding insurance policy; (2) how is the legal protection of mis-selling cases on unit linked insurance products based on Law No. 40/2014 regarding insurance policy. The type of this research is normative legal research. The source of data is classified into two types, there are primary legal source and secondary legal source. Meanwhile, the data collection of this research is collecting legal materials through inventory procedures and identification of laws and regulations. The data analysis technique used legal and descriptive interpretation analysis techniques. Based on an analysis conducted by the researcher, there are two research results, (1) arrangements for victims of mis-selling cases of Unit Link Insurance Products based on the insurance law using the services and facilities provided by OJK and legal protection for mis-selling victims both preventively and repressively based on the insurance law which is specified using OJK regulations.